2015
DOI: 10.1007/s10886-015-0644-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Timing of Herbivory on Plant Defense Induction and Insect Performance in Ribwort Plantain (Plantago lanceolata L.) Depend on Plant Mycorrhizal Status

Abstract: Plants often are exposed to antagonistic and symbiotic organisms both aboveground and belowground. Interactions between above- and belowground organisms may occur either simultaneously or sequentially, and jointly can determine plant responses to future enemies. However, little is known about time-dependency of such aboveground-belowground interactions. We examined how the timing of a 24 h period of aboveground herbivory by Spodoptera exigua (1–8 d prior to later arriving conspecifics) influenced the response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 69 publications
(101 reference statements)
2
47
1
Order By: Relevance
“…b). This contrasts to a study on Plantago lanceolata in which a longer time between the arrival of conspecifics caused a decrease in the consumption of leaf area by the second‐arriving Spodoptera exigua caterpillars (Wang et al ., ). However, in another study with S. exigua caterpillars attacking tomato plants twice, caterpillar bioassays after a short or longer period following the two attacks showed that a short arrival time after repeated attack yielded a lower plant resistance response than that after the first attack only (Underwood, ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…b). This contrasts to a study on Plantago lanceolata in which a longer time between the arrival of conspecifics caused a decrease in the consumption of leaf area by the second‐arriving Spodoptera exigua caterpillars (Wang et al ., ). However, in another study with S. exigua caterpillars attacking tomato plants twice, caterpillar bioassays after a short or longer period following the two attacks showed that a short arrival time after repeated attack yielded a lower plant resistance response than that after the first attack only (Underwood, ).…”
Section: Discussionmentioning
confidence: 97%
“…As plant responses to herbivores from different feeding guilds are often asymmetric (Kaplan & Denno, 2007), and we observed that the timing of herbivore arrival affects the performance of a subsequent herbivore (Wang et al, 2015), we expected an interaction between the effects of order and timing of inducer arrival on M. brassicae performance. Feeding by the aphid B. brassicae was expected to dampen the effect of P. xylostella induction, because of antagonistic effects of plant physiological responses of aphids to responses induced by caterpillars (Thaler et al, 2002;Voelckel & Baldwin, 2004;Stam et al, 2014).…”
Section: Time Of Arrival Of Inducing Herbivoresmentioning
confidence: 95%
See 1 more Smart Citation
“…We did not find correlations between foliar nutrient content and sequestration, potentially due to low sample sizes, but variation in soil N and P availability has been found to alter the efficiency of monarch caterpillar sequestration and the composition of cardenolides that monarch caterpillars sequester . Alternatively, interactions between AMF and caterpillar feeding may have altered the composition of foliar cardenolides Agrawal et al, 2014;Wang et al, 2015), resulting in the observed, AMF-mediated differences in caterpillar sequestration. However, milkweed responses to monarch caterpillar feeding can take up to 5 days to occur (Agrawal et al, 2014) and monarch caterpillars fed on our experimental plants for only 6 days.…”
Section: Sequestration By Specialist Herbivores Is Altered By Amf Avamentioning
confidence: 99%
“…A wide array of environmental factors have been shown to influence the types or concentrations of specialized metabolites produced by the model Plantago species, including plant/leaf age and phenology (Barton, 2008;Hanley et al, 2013;Pankoke et al, 2013;Sutter & Muller, 2011), herbivore and pest damage (Bowers, Collinge, Gamble, & Schmitt, 1992;Sutter & Muller, 2011), genotype (Adler, Schmitt, & Bowers, 1995;Al-Mamun, Abe, Kofujita, Tamura, & Sano, 2008;Barton, 2007;Marak, Biere, & van Damme, 2002;Zubair et al, 2012), habitat type (Adler et al, 1995), plant competition (Barton & Bowers, 2006;Pankoke, Hopfner, Matuszak, Beyschlag, & Muller, 2015;Waschke, Hancock, Hilker, Obermaier, & Meiners, 2015), associations with microorganisms including arbuscular mycorrhizal fungi (Bennett & Bever, 2007;Bennett, Macrae, Moore, Caul, & Johnson, 2013;Fontana, Reichelt, Hempel, Gershenzon, & Unsicker, 2009;Schweiger et al, 2014;Wang, Bezemer, van der Putten, & Biere, 2015), nutrient levels (Darrow & Bowers, 1999;Jarzomski, Stamp, & Bowers, 2000;Miehe-Steier, Roscher, Reichelt, Gershenzon, & Unsicker, 2015;Pankoke et al, 2015), UV levels (McCloud & Berenbaum, 1999;Murai et al, 2009), and variation in geography and climate (Mølgaard, 1986;Murai et al, 2009;Pellissier, Roger, Bilat, & Rasmann, 2014;Reudler & Elzinga, 2015).…”
Section: Introductionmentioning
confidence: 99%